The Influence of The Think Pair Share Cooperative Learning Model on The Ability of Mathematical Problem Solving in The System of Three Variable Linear Equations of Students in Class X of SMA Negeri 4 Pematang Siantar - Sinaga, Ruth Desti; Sidabutar, Ropinus; Marbun , Yanty Maria (Lembaga Riset Mutiara Akbar, 2023)
Based on the results of data analysis and discussion, it can be concluded that there is a positive and significant influence of the Think Pair Share cooperative learning model on mathematical problem-solving abilities in three-variable linear equation systems material for students in class X SMA Negeri 4 Pematang Siantar for the 2023/2024 academic year. This influence is shown through the regression equation Y= 1.447+ 0.714X. This influence is through the t-test, namely t-count > t-table (12.865 > 2.048) or p (sig.) < 0.05 (0.000 < 0.05) then H0 is rejected and H1 is accepted, which means there is an influence of the Think cooperative learning model Pair Share on mathematical problem-solving abilities in three-variable linear equation systems material for students in class X SMA Negeri 4 Pematang Siantar Academic Year 2023/2024. The contribution of variance of variable X (Think Pair Share cooperative learning model) to variable Y (problem solving ability) is 85.5%.